PROFITABILITAS, PERTUMBUHAN AKTIVA, UKURAN PERUSAHAAN, STRUKTUR AKTIVA, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PT BANK SYARIâ€™AH â€œXâ€ TBK.. - Susyanti, Jeni (IQTISHODUNA, 2008)
This research is aiming to know the influences of profitability, assets growth, enterprise dimension, assets structure, and the liquidity towards the financial capital structure. And to know the variable which has the most dominant influence towards PT. Bank Syariâ€™ah â€œXâ€, Tbk. This research has a dependent variable (financial capital structure) and independent variables (profitability, assets growth, enterprise dimension, assets structure, and liquidity). The analysis used to test the hypothesis is a double linear regression. The result of this research is that simultaneously (profitability, assets growth, enterprise dimension, assets structure, and liquidity). Are significantly influential towards financial capital structure with the R result square = 0,626. And partially profitable variable, assets growth, and liquidity are significantly influential towards financial capital structure, this is proved with the significant level of profitability = 0,009, of assets growth = 0,044, and of liquidity = 0,016. however, the variable of enterprise dimension and assets structure are not significantly influential towards the financial capital structure, this is proved with the value of sig (the enterprise dimension = 0,984, assets structure = 0,376) and the variable of profitability is most dominant negative influence with the value of t-stat -2,942 towards the financial capital structure.